Effect of Statin Therapy on Choroidal Structure in Patients with Hyperlipidemia: Case-Controlled Study with Optical Coherence Tomography - Hepokur, Mustafa; Yılmaz Çebi, Aslıhan; Çelebi, Medine Güneş; Salı, Fatma; Çelik, Fatma Betül; Oğuz, Halit (Cerrahpaşa Medical Journal, 2023)
Objectives: To investigate impact of statin therapy on choroidal structure. Methods: Case-controlled study included otherwise healthy patients with hyperlipidemia. 12 Patients with LDL levels below 210 mg/dl were treated with lifestyle changes, while 12 patients with levels above 210 mg/dl were additionally treated with atorvastatin. Optical coherence tomography images obtained at third month. Results: Choroidal thinning in the temporal region was observed in the statin group (p=0.031, p=0.033, p=0.029 at different measuring points). Total choroidal and luminal area were thinner in statin group (p=0.046 and p=0.049), while choroidal vascularity index remained same (p=0.853). Conclusion: It is uncertain whether choroidal thinning is mediated by decreased LDL levels or by decreased inflammation and oxidative stress. It may be advantageous to investigate statins in the management of pachychoroid spectrum disorders or oxidative stress-related diseases such as age-related macular degeneration.